Biventricular arrhythmogenic cardiomyopathy and sudden cardiac death: forensic perspectives based on autopsy case report - Nora Fnon; Hazem Ali; Athar M Khalifa; Enas M A Mostafa; Khadiga M Abdelrahman; Mahrous A Ibrahim (Egyptian Journal of Forensic Sciences)
Abstract Background Sudden cardiac death (SCD) is a leading global cause of mortality. Among its etiologies is arrhythmogenic cardiomyopathy (ACM), a relatively under-recognized and diagnostically challenging myocardial disorder characterized by fibrofatty replacement of one/both ventricles. Case presentation This study reported a case of a 50-years-old Egyptian male who experienced sudden death during a physical altercation. The absence of significant medical or familial histories highlighted the diagnostic challenges posed by biventricular ACM which in this case was identified only through postmortem examination. Biventricular ACM is a rare myocardial disorder involving both ventricles in which normal myocardial tissue is replaced by fibrofatty scar tissue. Autopsy of the present case revealed a mildly enlarged heart with a notable increase in epicardial fat. Histopathological analysis showed fibrofatty replacement of right ventricular (RV) myocardium reaching trabeculae and transmural in some areas. In the left ventricle (LV), subepicardial fibro-fatty infiltration and scattered fibrotic patches were observed. Focal lymphocytic inflammatory infiltrates were detected in the myocardium of both ventricles. Conclusion These findings were consistent with the characteristic pathological features of biventricular ACM. From a forensic standpoint, greater awareness of rare cardiomyopathies such as biventricular ACM among forensic pathologists can enhance diagnostic accuracy. Furthermore, the integration of postmortem genetic testing, where available, can facilitate the identification of genetic variants and enable more effective risk stratification and implementation of preventive measures in potentially at-risk family members.